Appréhender des « situations autoritaires ». Lectures croisées à partir du Cameroun et de l’Éthiopie - Marie Morelle; Sabine Planel (L'Espace Politique, 2018)
Introduction to the special issue “Playing with rules in authoritarian situations. Perspectives from Cameroon and Ethiopia.”